2018
DOI: 10.1080/14613808.2018.1507019
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent perceptions of singing: exploring gendered differences in musical confidence, identity and ambition

Abstract: This is a repository copy of Adolescent perceptions of singing: exploring gendered differences in musical confidence, identity and ambition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…This may be problematic, as customarily survey design recommends use of Likert-type scales (Likert, 1932) and some negatively worded questions to avoid automatic responses (DeVellis, 2012). Orton and Pitts (2019) surveyed adolescent perceptions of singing by asking English students in school Years 7, 8 and 9 (ages 12-14 years) to rate their enjoyment of various school-based and out-of-school music activities. The study reported a strong impact of motivation, confidence, selfefficacy and autonomy on the enjoyment of singing, with girls reportedly demonstrating more mature and flexible perceptions of singing.…”
Section: Survey Instruments In Music Researchmentioning
confidence: 99%
“…This may be problematic, as customarily survey design recommends use of Likert-type scales (Likert, 1932) and some negatively worded questions to avoid automatic responses (DeVellis, 2012). Orton and Pitts (2019) surveyed adolescent perceptions of singing by asking English students in school Years 7, 8 and 9 (ages 12-14 years) to rate their enjoyment of various school-based and out-of-school music activities. The study reported a strong impact of motivation, confidence, selfefficacy and autonomy on the enjoyment of singing, with girls reportedly demonstrating more mature and flexible perceptions of singing.…”
Section: Survey Instruments In Music Researchmentioning
confidence: 99%
“…Culturally meaningful experiences have been identified by Hampshire and Matthijsse (2010) as vital for building cultural capital in children. Friendships have been highlighted by (Clift et al, 2016;Fernández-Herranz et al, 2021), and adolescents and children (Parker, 2014;Orton and Pitts, 2019;Zhukov et al, 2021). While much of this research has been conducted via surveys, the findings presented here let us hear children's voices directly.…”
Section: Discussion Of Initial Analysismentioning
confidence: 81%
“…For example, Barrett (2011) described focus on "vocal production, music reading and interpretation, and performance practice" in the training of young cathedral choristers (p. 282). Orton and Pitts (2019) highlighted motivation as a strong influence on choristers' enjoyment of singing. Kirrane et al (2017) showed that effective team-work and leadership are essential elements of success in a professional chamber choir.…”
Section: Discussion Of Initial Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Papageorgi et al (2013) likewise established the same distinction between self-efficacy for learning and for performing, noting the latter’s close relation with stage fright (performance anxiety). Various other authors have underscored further aspects of musical competency in their respective scales, for example, Randles (2011), Upitis et al (2017), or Zelenak (2010) delve deeper into the components of self-efficacy or Ekinci (2014), Kurtuldu and Bulut (2017), Orton and Pitts (2019), or Watson (2010) develop specific scales related to musical or instrumental styles.…”
mentioning
confidence: 99%